Accelerating Parameter Mapping with a Locally Low Rank Constraint - Zhang, Tao (2014)
PURPOSE: To accelerate MR parameter mapping (MRPM) using a locally low rank (LLR) constraint, and the combination of parallel imaging (PI) and the LLR constraint. THEORY AND METHODS: An LLR method is developed for MRPM and compared with a globally low rank (GLR) method in a multi-echo spin-echo T(2) mapping experiment. For acquisition with coil arrays, a combined LLR and PI method is proposed. The proposed method is evaluated in a variable flip angle T(1) mapping experiment and compared with the LLR method and PI alone. RESULTS: In the multi-echo spin-echo T(2) mapping experiment, the LLR method is more accurate than the GLR method for acceleration factors 2 and 3, especially for tissues with high T(2) values. Variable flip angle T(1) mapping is achieved by acquiring datasets with 10 flip angles, each dataset accelerated by a factor of 6, and reconstructed by the proposed method with a small normalized root mean square error of 0.025. CONCLUSION: The LLR method is likely superior to the GLR method for MRPM. The proposed combined LLR and PI method has better performance than the two methods alone, especially with highly accelerated acquisition.